Attribute-based fully homomorphic encryption scheme over rings - Yong-hui ZHENG; Yuan-ji KANG; Chun-xiang GU; Hui DONG (Tongxin xuebao)
The fully homomorphic encryption has important applications in the area of data security and privacy security of cloud computing,but the size of secret keys and ciphertext in most of current homomorphic encryption schemes were too large,which restricted its practical.To improve these drawbacks,a recoding scheme and a attribute-based encryption scheme based on learning with errors problem over rings were provided,then a attribute-based fully homomorphic encryption was constructed.The new scheme overcame the above mentioned drawbacks,because it did't need public key certificate,meanwhile,it can achieve the fine-grained access control to the ciphertext.Compared with similar results,proposed method decreases the size of keys and ciphertext greatly.